2014
DOI: 10.1111/1471-0528.12964
|View full text |Cite
|
Sign up to set email alerts
|

A follow‐up of a randomised study of metformin and insulin in gestational diabetes mellitus: growth and development of the children at the age of 18 months

Abstract: Objective To compare the growth and development of children born to mothers with gestational diabetes mellitus (GDM) requiring pharmacological treatment, and randomised to treatment with metformin or insulin.Design Follow-up of a randomised controlled trial (RCT) comparing metformin and insulin treatment of GDM.Setting Data were gathered during routine visits to child welfare clinics at the ages of 6, 12, and 18 months, including weight and height measurements, and assessment of motor, social, and linguistic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
111
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(118 citation statements)
references
References 20 publications
4
111
3
Order By: Relevance
“…19 Seventy four percent of invited children attended to our study, the study population (146 children) being larger than in previous studies evaluating the effect of metformin use during pregnancy to neurodevelopment of offspring. 11,15 In addition, we applied standardized and internationally used neurodevelopmental and neurological tests. The limitation of the study is that the sample size, although adequate for detecting medium or large group differences, may not be adequate for detecting small differences between groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Seventy four percent of invited children attended to our study, the study population (146 children) being larger than in previous studies evaluating the effect of metformin use during pregnancy to neurodevelopment of offspring. 11,15 In addition, we applied standardized and internationally used neurodevelopmental and neurological tests. The limitation of the study is that the sample size, although adequate for detecting medium or large group differences, may not be adequate for detecting small differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, there are only 2 follow-up studies 14,15 of children born to patients with gestational diabetes mellitus (GDM) treated with metformin or insulin. In the largest follow-up study of Metformin in Gestational diabetes (MiG) study, 1 the body composition was measured at the age of 2 years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One study found no differences in motor, social or linguistic development at 18 months of age [47]. In the same study, the degree of adiposity was similar in both the metformin and insulin groups, but children exposed to metformin antenatally were heavier at the age of 12 months and both taller and heavier at the age of 18 months [47].…”
Section: Medical Treatment Of Gdmmentioning
confidence: 91%
“…Until now, offspring exposed to metformin have been found to have more favourable fat distribution, and similar blood pressure at the age of 2 years compared with offspring in the insulin group [45,46]. One study found no differences in motor, social or linguistic development at 18 months of age [47]. In the same study, the degree of adiposity was similar in both the metformin and insulin groups, but children exposed to metformin antenatally were heavier at the age of 12 months and both taller and heavier at the age of 18 months [47].…”
Section: Medical Treatment Of Gdmmentioning
confidence: 99%